Towards an insight on the photoluminescence of disordered CaWO4 from a joint experimental and theoretical analysis - Orhan, E.; Anicete-Santos, M.; Maurera, MAMA; Pontes, F. M.; Souza, A. G.; Andres, J.; Beltran, A.; Varela, José Arana [UNESP]; Pizani, P. S.; Taft, C. A.; Longo, Elson [UNESP] (Elsevier B.V., 2005)
A joint experimental and theoretical study has been carried out to rationalize for the first time the photoluminescence (PL) properties of disordered CaWO4 (CWO) thin films. From the experimental side, thin films of CWO have been synthesized following a soft chemical processing, their structure has been confirmed by X-ray diffraction data and corresponding PL properties have been measured using the 488 nm line of an argon ion laser. Although we observe PL at room temperature for the crystalline thin films, the structurally disordered samples present much more intense emission. From the theoretical side, first principles quantum mechanical calculations, based on density functional theory at B3LYP level, have been employed to study the electronic structure of a crystalline (CWO-c) and asymmetric (CWO-a) periodic model. Electronic properties are analyzed in the light of the experimental results and their relevance in relation to the PL behavior of CWO is discussed. The symmetry breaking process on going from CWO-c to CWO-a creates localized electronic levels above the valence band and a negative charge transfer process takes place from threefold, WO3, to fourfold, WO4,. tungsten coordinations. The correlation of both effects seems to be responsible for the PL of amorphous CWO. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: ab initio calculations; ceramics; crystals; photoluminescence; thin layers